+0  
 
0
354
2
avatar
how do you do this?


4(m - 3) = 12
Guest Mar 4, 2012
 #1
avatar+18 
0
Math:

how do you do this?


4(m - 3) = 12





very easy:12:4=3 that means that you need three in the ()! only 6-3=3 = m=3
Mathefreak mal pi  Mar 4, 2012
 #2
avatar+3079 
0
[input]4(x - 3) = 12[/input]

4(m - 3) = 12
4m-3*4=12
4m-3*4+3*4=12+3*4
4m=12+3*4=12+12=24
4m/4 = 24/4
m = 6
admin  Mar 4, 2012

18 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.